ANALISIS YURIDIS MENGENAI UPAH MINIMUM KABUPATEN/KOTA YANG DITETAPKAN PERATURAN GUBERNUR DAN DAMPAKNYA TERHADAP PEKERJA DAN PERUSAAAN (WILAYAH KAJIAN DI KABUPATEN MALANG) - Fatkhurohman, Andika Kurniawan dan (Jurnal Konstitusi, 2011)
Development in the manpower field is intended to improve the workers’ welfare. One of the efforts made to promote the welfare is to implement the policies on wages though minimum wage. However, the minimum wage is very crucial to standardize in a policy, since such a minimum wage stands on the two opposing interest. Therefore, if the conflicts of interest between the two is not accommodated in the policy, it will create a boomerang for the condition of industrial relation and the economy in the province in general and especially City/Regency.